ANALISIS SIKAP DAN PERILAKU KONSUMEN TERHADAP PRODUK DONAT PAKET SURYA BAKERY DI KOTA BENGKULU - Fridinawati, Dwita; Priyono, Basuki Sigit (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2012)
One form of agro-processing industry is donuts. The bakery is one business that is engaged in the fulfillment of their needs and as a tangible example of product development of agricultural products, which also had a very tight competition from time to time. The research was conducted in February-March 2012 in the city of Bengkulu with the aim of knowing the attitudes and behavior of consumers towards the product package Surya donut bakery in the city of Bengkulu. Overall the total consumer attitude (AB) to the product package Surya donut bakery in the city of Bengkulu is positive with a total value of (10.289), The results obtained for the consumer behavior towards Surya bakery donut package is positive with a value of (7.5914), which indicates that consumer attitudes (AB), which results either positive or no consistent relationship to consumer behavior (B), which also results in a positive or good.Keywords: Consumer attitude and behaviour, value added, Product development process